Paediatric tracheostomy and ventilation home care with challenging socio-economic circumstances in South Africa. (May 2016) - Groenendijk, Ilse; Booth, Jane; van Dijk, Monique; Argent, Andrew; Zampoli, Marco
Abstract: Background: Children discharged home with a tracheostomy need a safe home environment and access to health care. We described the indications, clinical characteristics, socio-economic circumstances and outcomes of children enroled in a tracheostomy home care programme in South Africa. Methods: We performed a retrospective chart review of children receiving a tracheostomy and enroled in the Breatheasy programme at the Red Cross War Memorial Children's Hospital, Cape Town. Medical and background characteristics were recorded. Influences of socio-economic variables and underlying medical conditions on length of hospital stay, unplanned readmissions and mortality in the first year after discharge were evaluated. Results: In the period 2008–2012, 157 patients were discharged home with a tracheostomy. Median hospital stay after tracheostomy insertion was significantly longer when parents had incomplete schooling compared to completed secondary school or higher education; 30 days (IQR 21–53) versus 23 days (IQR 16–33), respectively. Unplanned readmissions in the first year were documented for 72 patients (45.9%). The risk for unplanned readmission was 2.6 times higher in families with substance abuse the risk of respiratory infections was two-fold in case of household cigarette smoke exposure (OR 2.3.) Tracheostomy-related mortality was low (1.2%). An underlying medical condition was the only independent significant risk factor for mortality (OR 5.1, 95% CI 1.8–14.3). Conclusion: This study demonstrates that despite difficult socio-economic circumstances, home ventilation of children with a tracheostomy is safe, provided caregivers are adequately trained and supported.